Team Communication as a Collaborative Process - Gervits, Felix; Eberhard, Kathleen; Scheutz, Matthias (Frontiers in Robotics and AI, 2016)
Communication channels can reveal a great deal of information about the effectiveness of a team. This is particularly relevant for teams operating in performance settings such as medical groups, military squads, and mixed human-robot teams. Currently, it is not known how various factors including coordination strategy, speaker role, and time pressure affect communication in collaborative tasks. The purpose of this paper is to systematically explore how these factors interact with team discourse in order to better understand effective communication patterns. In our analysis of a corpus of remote task-oriented dialogue (CReST corpus), we found that a variety of linguistic- and dialogue-level features were influenced by time pressure, speaker role, and team effectiveness. We also found that effective teams had a higher speech rate, and used specific grounding strategies to improve efficiency and coordination under time pressure. These results inform our understanding of the various factors that influence team communication, and highlight ways in which effective teams overcome constraints on their communication channels.